Popularization of Semarang Spring Rolls Outside the Chinese Community, 1963-1986 - Dianing Wuri Handayani; Putri Agus Wijayati (Universitas Hamzanwadi, 2026)
This study examined the popularization of Semarang lumpia outside the Chinese community during the period 1963-1968 by placing it within the socio-political context of the New Order. In the context of Semarang lumpia, it explains how this culinary dish, originating from Peranakan Chinese cuisine, was accepted across ethnic groups and became a symbol of the city's identity. This study used a qualitative method with a historical approach, encompassing heuristics, criticism, interpretation, and historiography. The results show that during the New Order era, the Chinese community's freedom of movement was restricted, but they still had their economic freedom to continue their business. Since the 1970s, the popularization of Semarang lumpia has gradually increased, involving production adaptations, expanded distribution, and the normalization of consumption in public spaces. Within the context of restrictions on Chinese cultural expression, lumpia remained relatively safe because they did not display specific identity symbols. Until the 1980s, the popularization of lumpia increased further following a shift in the narrative from ethnic cuisine to Semarang's signature cuisine.